On-farm phenotypic characterization of cattle genetic resources in south and north Wollo Zones of Amhara Region, north eastern Ethiopia - Tadesse, D.; Ayalew, W.; Hegde, B.P. (2008)
Economic comparisons among Ethiopian Boran and their crosses with HolsteinFriesian were made in the central highlands of Ethiopia. Data collected fromexperimental dairy cattle herds of the International Livestock Research Institute(ILRI) at the Debre Zeit Research Station, Ethiopia were used. The data of oneyear (2003 calendar year) were used for calculation of costs and returns.Comparisons of economic performance of the different genetic groups (EthiopianBoran, 50, 75 and 87.5 per cent Holstein Friesian Inheritances) were madethrough calculations of profit per day per cow, profit per year per cow and cost perliter of milk production. The results indicated that the cost required to produce aliter of milk was significantly higher (P<0.01) for the Ethiopian Boran breedcompared to all crosses. Ethiopian Boran cattle required more than double theamount required by the crosses. The costs were estimated at ETB† 3.17, 1.32, 1.39and 1.17 for Ethiopian Boran, 50%, 75% and 87.5% crosses, respectively. Profitper day per cow and profit per year per cow were also much lower for EthiopianBoran (ETB1.15 and 45.8, respectively) compared with the crosses (ETB15.3 and4109.6 for 50%, 17.6 and 4760.6 for 75%, and 21.0 and 5700.7 for 87.5%,respectively) (P<0.01). The profit per day and profit per year for the 87.5%crossbreds were higher (P<0.05) than the amount for the 50% crossbreds. The 75%crosses did not have a significant (P>0.05) difference with 50 and 87.5% exoticblood levels. It was concluded that intensive dairy production with indigenoustropical breeds (Ethiopian Boran) is not economically feasible. Therefore, in suchproduction systems crossbreds should be utilized.Economic comparisons among Ethiopian Boran and their crosses with HolsteinFriesian were made in the central highlands of Ethiopia. Data collected fromexperimental dairy cattle herds of the International Livestock Research Institute(ILRI) at the Debre Zeit Research Station, Ethiopia were used. The data of oneyear (2003 calendar year) were used for calculation of costs and returns.Comparisons of economic performance of the different genetic groups (EthiopianBoran, 50, 75 and 87.5 per cent Holstein Friesian Inheritances) were madethrough calculations of profit per day per cow, profit per year per cow and cost perliter of milk production. The results indicated that the cost required to produce aliter of milk was significantly higher (P<0.01) for the Ethiopian Boran breedcompared to all crosses. Ethiopian Boran cattle required more than double theamount required by the crosses. The costs were estimated at ETB† 3.17, 1.32, 1.39and 1.17 for Ethiopian Boran, 50%, 75% and 87.5% crosses, respectively. Profitper day per cow and profit per year per cow were also much lower for EthiopianBoran (ETB1.15 and 45.8, respectively) compared with the crosses (ETB15.3 and4109.6 for 50%, 17.6 and 4760.6 for 75%, and 21.0 and 5700.7 for 87.5%,respectively) (P<0.01). The profit per day and profit per year for the 87.5%crossbreds were higher (P<0.05) than the amount for the 50% crossbreds. The 75%crosses did not have a significant (P>0.05) difference with 50 and 87.5% exoticblood levels. It was concluded that intensive dairy production with indigenoustropical breeds (Ethiopian Boran) is not economically feasible. Therefore, in suchproduction systems crossbreds should be utilized.